Optical Properties and UV Sensing Response of Nitrogendoped TiO2 Thin Film by CVD - Siowwoon, Ng; Sau, Siong Tneh; Fong, Kwong Yam; Hassan, Zainuriah (2017)
This work was demonstrated a cold-wall chemical vapour deposition (CVD) setup to prepare nitrogen (N)-doped titanium dioxide (TiO2) thin film on glass substrates, which presents semi-transparent yellowish surface. The prepared N-doped TiO2 film is homogeneous and possesses polycrystalline anatase structure. The transmittance measurement was carried out in the ultraviolet-visible spectral region to evaluate the film thickness, optical constants, and the optical band gap was determined by Tauc plot. A metal-semiconductor-metal (MSM) ultraviolet (UV) photodetector by the Pt/N-doped TiO2 film has shown a positive response towards UV illumination.